HUBUNGAN ANTARA PEMBERIAN MAKANAN DAN TINGKAT PENDAPATANKELUARGA DENGANSTATUS GIZI ANAK BALITA DI KECAMATAN MUARASIPONGI KABUPATEN MANDAILING NATAL - Annisa Ayu Rahma; Etti Sudaryati; Jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Health problems are still common in Indonesia, including nutritional problems in toddlers. One of the problems that often found in children under five of them malnutrition. Malnutrition in children can lead to disruption of growth and development and susceptible to infectious diseases. Malnutrition in children can be caused by inadequate feeding and economic factors. The purpose of the study was to analyze the relationship between feeding and family income levels with nutritional status of children under five in Muarasipongi Sub-district, Mandailing Natal Regency in 2017. The type of research used quantitative research with cross sectional design. Sampling using multistage random sampling technique with a sample of 88 children. Data collection was done by direct interviews on mothers with children under five using structured questionnaires. Feeding of children was seen using 24-hour recall form and food frequency. The nutritional status of children is seen by measuring body weight and height of the child. To see the relationship between feeding and family income level with nutritional status of children under five using Chi Square test with 95% confidence level. The results showed that based on nutritional status with index weight for age (W/A) related to the completeness of food type, energy sufficiency level, carbohydrate, protein and family income. Based on the height for age (H/A) index associated with the completeness of food type, the level of energy adequacy, protein, vitamin A, and zinc. Based on the index weight for height (W/H) associated with the level of carbohydrate adequacy, protein and family income. The p value obtained for the relationship between feeding and family income levels with nutritional status was (p <0.05). The frequency of feeding is seen from the consumption of rice each day. The most frequent frequency of side dishes is eggs. Vegetables are often consumed by children is cassava leaves, children also consume crackers every day. Suggestions in this study to the Health Office and public health center to socialize balanced nutrition through a balanced nutrition handbook for health workers for cadres to keep voicing about balanced nutrition in the community. Keywords: family income, nutritional status, under five children feeding